2009
DOI: 10.1186/1475-2891-8-24
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of enteral nutrition with combined enteral and parenteral nutrition in post-pancreaticoduodenectomy patients: a pilot study

Abstract: Background: Many clinical studies have demonstrated that early postoperative enteral nutrition (EN) improved the postroperative course. Post-pancreaticoduodenectomy (PD), patients tend to suffer from postoperative nausea, abdominal distention, and diarrhoea, causing difficulty in the introduction of EN. In this pilot study, we investigated the appropriate nutritional mode postpancreatic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
6

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 15 publications
0
19
0
6
Order By: Relevance
“…A total of 51 articles were utilized for the review, with 14 addressing malnutrition and pancreatic dysfunction at pancreatic cancer diagnosis [13,14,15,16,17,18,19,20,21,22,23,24,25,26]; 19 addressing pancreatic dysfunction after surgery [27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45], including 10 which also discussed preoperative dysfunction and nutrition [27,30,31,32,33,35,37,39,40,41]; and 18 addressing nutritional intervention [11,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62] (Figure 1). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 51 articles were utilized for the review, with 14 addressing malnutrition and pancreatic dysfunction at pancreatic cancer diagnosis [13,14,15,16,17,18,19,20,21,22,23,24,25,26]; 19 addressing pancreatic dysfunction after surgery [27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45], including 10 which also discussed preoperative dysfunction and nutrition [27,30,31,32,33,35,37,39,40,41]; and 18 addressing nutritional intervention [11,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62] (Figure 1). …”
Section: Resultsmentioning
confidence: 99%
“…Clinicians have also tried a dual EN + TPN strategy to optimize postoperative nutritional status. Nagata et al reported that patients who received EN with TPN, had a significantly higher rate of duration and discontinuance of enteral feeding, compared to those who just received EN [50]. There were no differences in postoperative morbidity, catheter-related infections, percent of weight loss, and postoperative length of stay.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, most clinical studies have not been able to demonstrate the effectiveness of EN in the clinical course of these patients [9][10][11][12][13][14][15]. Shen et al reported that EN appeared safe and tolerable for patients after pancreatoduodenectomy, but they did not show advantages in terms of infectious complications and postoperative hospital stay by accumulation of data from recent RCTs [16].…”
Section: Discussionmentioning
confidence: 99%
“…However, postoperative total enteral feeding is associated with complications such as diarrhea, abdominal distention and abdominal cramps. These symptoms worsened with increasing caloric intake and finally lead to discontinuance of enteral feeding 4 . Also, gastroparesis is a frequent postoperative event following pancreatoduodenal resection, and this often necessitates prolonged gastric decompression and EN support 5 .…”
Section: Introductionmentioning
confidence: 99%